Xenotransplantation of pancreatic islets microencapsulated in agarose gel - Gabr, Mahmoud M; Bakr, Mohamed A; El-Baz, Mahmoud A; Ghoneim, Mohamed A (African Journal of Nephrology, 2023)
Prevention of rejection is critical to achieve successful pancreatic islet transplantation. Protection of islet cells from rejection by isolating the islets in artificial membranes has been used instead of immunosuppression treatment. In this study we investigated the microcapsulation of hamster islets in hydrophilic microcapsules made of agarose. The microcapsulated hamster islets were placed intraperitoneally in mice in which diabetes was induced by a single dose (150 mg/kg of body weight) of streptozotocin. Five groups were studied. The first group (5 mice) received free hamster islets (1000 islets). The second group (5 mice) received 1000 empty agarose microcapsules and 1000 free hamster islets. The third group (10 mice) received hamster islets microencapsulated in agarose (500 microcapsules). The fourth group (10 mice) received 1000 islet microcapsules. The fifth group (10 mice) received 1000 islet microcapsules cultured in CMRL-1066 medium for 4 weeks at 37°C. Mice of group 1 and group 2 failed to achieve normoglycemia. Recipient mice received microencapsulated islets (group 3,4,5) maintained normoglycemia for a mean of 45 ± 5 days (range 30-65 days). These cured mice had normal glucose tolerance tests, which indicates that islets in the microcapsules were functioning as if they are in an intact pancreas. Microcapsules, retrieved up to 30 days after transplantation, showed no evidence of tissue reaction. Our study indicates that agarose microcapsules can protect islet xenografts from rejection. These microcapsules may be suitable for human clinical islet xenotransplantation.